Machiavelli and Max Weber: ethics and political realism - Guimarães, Carlos Nunes (Argumentos - Revista de Filosofia, 2010)
Men are inevitably tied to politics. This activity is inherent to the very condition of human beings compelled to live in society. Many factors do exist, however, contributing to the misinterpretations of politics that is not seen as an indispensable activity to the resolution of conflicts and a path to man’s full development potentialities as a social being. A major aspect leading to the understanding of politics is its relation to ethics which has acquired a new dimension following an analysis based on realism. Political realism as propounded by Machiavelli and later by the German philosopher Max Weber will have an impact on the concept of idealized politics which is capable of producing goodness only by the treading of a virtuous path. To Machiavelli’s thinking, the supreme goodness to be preserved is the State, and to reach this end one is not supposed to be led by ethical manners that hinder the struggle for defense of the Reason of State. Four centuries later, Weber will give shelter to this idea by proposing that there exist ethics of conviction and ethics of responsibility. The first is established a priori, the second is the one that will be measured by the outcome of actions originating from the political field.